Employment of English Language Teachers in an EFL Context: Perspectives From School Administrators - Sibel Tatar (Universidad Nacional de Colombia, 2019)
This paper presents a study on the employment criteria used by school administrators and their views on the strengths and weaknesses of local teachers and expatriate teachers. This study aimed to provide a perspective on the issue from an English as a foreign language context. Questionnaires collected from administrators of 94 private primary and high schools in Istanbul were analyzed. Although being a native speaker of English ranked seventh out of the eight criteria, the presence of expatriate teachers in a school was considered important. In addition, participants from schools that employed both expatriate and local teachers attributed more importance to the native-speakerness criterion. Finally, administrators found local teachers more knowledgeable in teaching methods, whereas expatriate teachers were perceived as better in language use.